MORPHOLOGICAL STUDY OF BICONTINUOUS CONCENTRIC LAMELLAR (BCL) NANOSTRUCTURED SILICA KCC-1 SYNTHESIZED AT ATMOSPHERIC PRESSURE - Arsyad, Rafiq
Mesoporous silica is an oxide material with pore size from 2 to 50 nm and has a wide range of morphologies and application. Various types of mesoporous silica have been discovered, including SBA-15, MCM-41, FSM-16, and KCC-1. In this research, mesoporous silica that will be studied is mesoporous silica with dendritic fibrous morphology or known as KCC-1. KCC-1 can be used for various applications because it has an open three-dimensional pore structure that results in better access to the particles’ inner surface than other types of silica. Generally, KCC-1 is synthesized by the solvothermal method at high pressure. However, the solvothermal process has some drawbacks, including scalability, continuity, and cost-and- time-effectiveness. Since KCC-1 has vast applications, a more efficient and effective way of synthesis is required. This research investigates the KCC-1 synthesis method, which is better and more effective and can be upscaled more easily, namely the reflux method. SEM and TEM analysis characterized the KCC-1 particles to determine the particle morphology, particle size, lamella’s thickness, and lamella’s concentricity. Lamellae’s cross-sectional area analysis was performed on SEM images using ImageJ software to discover the features of the KCC-1 particle binary images to compare the morphology between one particle with the particles synthesized in other condition. The TiO2 anatase coating process on the surface of KCC-1 particles was successfully conducted to result in KCC-1/TiO2 particles; however, its photocatalytic activity with respect to the TiO2 anatase phase has to be verified.